Policy on the Development of the Law Laboratory as a Center for Legal Studies and Advocacy (Law Laboratory Study, Faculty of Law, University of Jambi) - Muskibah, Muskibah; Umar, Umar; Hidayah, Lili Naili (Journal of Law, Politic and Humanities, 2025)
The purpose of this study is to analyze the function of the law laboratory based on education, research, and community service, as well as analyze what factors can affect the strengthening and legal laboratory as a center for legal studies and advocacy. This legal research uses empirical juridical research, using a legislative approach and a conceptual approach. The object of the research is the law laboratory, Faculty of Law, University of Jambi. The analysis was carried out qualitatively and presented in a qualitative descriptive manner. The results of the research on the law laboratory of the Faculty of Law, University of Jambi, that the laboratory at the faculty of law has not implemented the provisions of the Regulation of the Minister of Education and Culture Number 19 of 2014 concerning the Organization and Work Procedures of the University of Jambi and the Regulation of the Rector of the University of Jambi Number 5 of 2022 concerning the Organizational Structure, Work Procedures, Duties and Functions of the Faculty of Law, University of Jambi.